2007
DOI: 10.1016/j.jmp.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of base time for redundant signals experiments

Abstract: We report analytical and computational investigations into the effects of base time on the diagnosticity of two popular theoretical tools in the redundant signals literature: (1) the race model inequality and (2) the capacity coefficient. We show analytically and without distributional assumptions that the presence of base time decreases the sensitivity of both of these measures to model violations. We further use simulations to investigate the statistical power model selection tools based on the race model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…For example, in a group of participants who exhibited super capacity, the withinchannel processing rate for double targets was estimated as substantially higher than the single-target rate, meaning that each channel actually performed better when the other channel was activated. Base times, however, were almost identical and could not account for the observed super capacity, in complete agreement with Townsend and Honey's (2007) conclusion.…”
Section: Influence Of Base Times On Capacity Measuressupporting
confidence: 70%
See 3 more Smart Citations
“…For example, in a group of participants who exhibited super capacity, the withinchannel processing rate for double targets was estimated as substantially higher than the single-target rate, meaning that each channel actually performed better when the other channel was activated. Base times, however, were almost identical and could not account for the observed super capacity, in complete agreement with Townsend and Honey's (2007) conclusion.…”
Section: Influence Of Base Times On Capacity Measuressupporting
confidence: 70%
“…Interestingly, this is just the opposite of what occurs in OR designs (cf. Townsend & Honey, 2007). This reversed role of the base time can be of assistance in assessing the magnitude of its influence and its relative contribution in the OR vs. AND paradigms.…”
Section: Appendix 3 the Standard Parallel Model And Assay Of Base Timmentioning
confidence: 98%
See 2 more Smart Citations
“…However, in practice, the capacity coefficient may be confounded by differences in "base time" (i.e., the time to complete early sensory and response preparation and execution processes) and speed-accuracy trade-off between conditions contributing to C(t). Townsend and Honey (2007) investigated base time effects and concluded that they are unlikely to be problematic. 2 Similarly, the design used in the OR redundant-target task, where double-and single-target conditions are randomized within blocks of trials, makes confounding from speed-accuracy trade-off unlikely, since it is usually assumed that participants can change trade-off strategies only if they can anticipate upcoming conditions (Ratcliff, 1978).…”
Section: Lba Redundant-target Task Modelmentioning
confidence: 99%